Complex Deformation of Critical Kähler Metrics (Journal of Mathematical Study, 2017)
In this paper, we use Pacard-Xu's methods to discuss the complex deformationof constant scalar curvature metrics in the case of fixed and varying complexstructures. Moreover, we also discuss the complex deformation of Kähler-Ricci solitons.
Keywords: Complex deformation; constant scalar curvature metrics; Kähler Ricci solitons; extremal solitons.